2023
DOI: 10.1101/2023.10.13.562139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual Ethanolamine Head Groups in Ionizable Lipids Facilitate Phospholipid-free Stable Nanoparticle Formulation for Augmented and Safer mRNA Delivery

Jing Lu,
Ting Jiang,
Xuechun Li
et al.

Abstract: The accelerated advent of mRNA-based therapeutics and vaccines, highlighted by the battle against SARS-CoV-2, underscores the urgency to refine lipid nanoparticles (LNPs) for efficient mRNA delivery. In this work, we introduce a novel series of ionizable lipids characterized by double ethanolamine head groups, significantly amplifying mRNA binding affinity. A succinct three-component formulation is subsequently delineated, obviating the conventional dependency on phospholipids inherent in traditional four-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Despite that researchers have most recently reported that iPLX phospholipid-free LNP systems presented exceptional stability [ 28 ], superior mRNA encapsulation efficiency, and sustained robust delivery efficacy, the three FDA-approved LNP-RNA products as well as most LNP-mRNA in preclinical reports conventionally are constituted of four components: ionizable or cationic lipids, sterols, helper lipids, and PEGylated lipids. To better illustrate the conceptions, the lipids mentioned in this review were demonstrated in Fig.…”
Section: Lipid and Lnp Formulations For Mrna Medicinesmentioning
confidence: 99%
“…Despite that researchers have most recently reported that iPLX phospholipid-free LNP systems presented exceptional stability [ 28 ], superior mRNA encapsulation efficiency, and sustained robust delivery efficacy, the three FDA-approved LNP-RNA products as well as most LNP-mRNA in preclinical reports conventionally are constituted of four components: ionizable or cationic lipids, sterols, helper lipids, and PEGylated lipids. To better illustrate the conceptions, the lipids mentioned in this review were demonstrated in Fig.…”
Section: Lipid and Lnp Formulations For Mrna Medicinesmentioning
confidence: 99%